Learning the concept of two-dimensional figure through Borobudur artifacts for lower graders of elementary school mathematics - Azamul Fadhly Noor Muhammad; Marsigit Marsigit; Soeharto Soeharto (Universitas negeri Yogyakarta, 2021)
Important changes in mathematics teaching need to be made to accommodate the constantly changing students’ demography in the lower grades of Elementary Schools, particularly in mathematics competence. Teachers must contextualize mathematics learning by linking mathematics content to the culture and real-life experiences of low-grade students at the Elementary School level. Mathematical concepts taught in elementary schools shall be relevant with students' personal experiences in everyday life. Throughout history, mathematics has been widely used by different groups in a variety of ways. Arithmetic and geometry are used to meet the daily needs of society, both culturally and socially. Ethnomathematics is defined as the way people from different cultures use mathematics in their daily lives. Elementary school students are only required to learn the concept of simple two-dimensional figure in their mathematics learning. Some complexities in this topic are related to the way to deal with irregular shape of two-dimensional figures or the different length of the sides, which can actually be solved through the removal or addition of the different parts of the shape to resemble the main shape.